أثر تغیرات سعر الصرف على أرصدة میزان المدفوعات الجزائري -دراسة قیاسیة باستخدام نماذج أشعة الانحدار الذاتي) (VARخلال الفترة -201 - عبد المجید عبود (Finance and Business Economies Review, 2023)
This study aims at highlighting the impact of exchange rate changes on balance of payments balances in Algeria through annual data covering the period 1990-2015 using the standard approach , vector regression models, variance analysis and response functions. The study was based on two variables The official exchange rate and oil prices in the interpretation of both balance of trade balance and total balance of payments balance, while based on the exchange rate variables and external debt service in the interpretation of movements of capital account balance, and we concluded that there is little impact of exchange rate changes on balance Header account The results of the variance analysis showed that the contribution of the exchange rate is moderate in explaining the error of forecasting the balance of trade and the total balance, in contrast to the oil price variable, which has a great predictive ability to explain this and a greater contribution to balance of payments stability, This is because the Algerian economy is a oil economy.